Pine-Oil-Derived Sodium Resinate Inhibits Growth and Acid Production of Streptococcusmutans In Vitro - Rajala, Otto (My University, 2024)
S. mutans is a key pathogen in dental caries initiation and progression. It promotes oral biofilm dysbiosis and biofilm acidification. Sodium resinate is a salt of pine-oil-derived resin which has antimicrobial properties. Pine-oil-derived resin consists of terpenes, diterpenes, and abietic acids. The aim of this study was to determine the effects of pine (Pinus sylvestris) oil resinate (RS) on growth and acid production of cariogenic S. mutans strains in planktonic form and biofilm. The S. mutans type strain NCTC10449 and clinical isolate CI2366 were grown on 96-well plates for testing of RS effects on growth and biofilm formation, and on plates with integrated pH-sensitive optical ensors for real-time measurements of the effects of RS on bacterial acid production. We found that even short-time exposure to RS inhibits the growth and acid production of S. mutans in the planktonic phase and biofilms. In addition, RS was able to penetrate the biofilm matrix and reduce acid production inside S. mutans biofilm. RS thus shows potential as a novel antibacterial agent against cariogenic bacteria in biofilm.
Keywords: Streptococcus mutans, sodium resinate, Pinus sylvestris, acid production, oral biofilm, caries, optical pH sensors